‘Publish or Perish’ Trend: Fueling the Predatory Journals - Atreya, Alok (Journal of Lumbini Medical College, 2020)
In the past, journals were published only in the print, and the only way to access them was through the library. However, today we can easily access journals and articles with a click. There are more online journals which have made it possible and feasible for authors to submit their work.